ROS-scavenging hydrogel to promote healing of bacteria infected diabetic wounds - Zhao, He; Huang, Jie; Li, Yan; Lv, Xinjing; Zhou, Huiting; Wang, Hairong; Xu, Yunyun; Wang, Chao; Wang, Jian; Liu, Zhuang (Biomaterials, 2020)
Bacterial infection has been a great threat to dermal wounds, especially to difficult-to-heal diabetic wounds. It is known that reactive oxygen species (ROS) generated by wounds or bacterial infection could further impede wound healing. Here, a type of ROS-scavenging hydrogel is developed by using polyvinyl alcohol (PVA) cross-linked by a ROS-responsive linker. The obtained hydrogel could act as an effective ROS-scavenging agent to promote the wound closure by decreasing the ROS level and up-regulating M2 phenotype macrophages around the wound. Importantly, such hydrogel formed in the wound could allow release of therapeutics, including mupirocin to kill bacteria, and granulocyte-macrophage colony-stimulating factor (GM-CSF) to accelerate the wound closure, in responsive to endogenous ROS existing in the wound microenvironment. Remarkably, our drug-loaded ROS-scavenging hydrogel could be employed to effectively treat various types of wounds including difficult-to-heal diabetic wounds with bacterial infection. Therefore, this work presents an effective strategy based on ROS-scavenging hydrogel for wound healing under various kinds of complications. [Display omitted]